Implementation of E-procurement for construction materials [electronic resource] - Ling, Steven Hoe Khing, 1986-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2011